MODEL PEMBELAJARAN TERPADU BERBASIS SENTRA PADA PAUD RUMAH KITA SEMARANG - Ismatul Khasanah; Venty . (Universitas PGRI Semarang, 2014)
This research is motivated by how important requirement of education model, because of the successful nation only be generated through education. Education for early childhood in coaching efforts aimed at children from birth to six years old conducted through giving educational stimulation to help the growth and development of children's physical and spiritual in order to be ready to enter further study (Depdiknas: 2003). The objectives of this research is to find the integrated model based learning center at PAUD Rumah Kita Semarang. This study is a qualitative research by using phenomenological naturalistic approach. 1) Data collection 2) exploration 3) researchers conducted a focused research related to integrated model based learning centers. Data collection techniques applied in this study was: observation, interviews and questionnaires, documentation. The result of this research shown that Integrated learning conducted at PAUD Rumah Kita is a holistic learning system, which combines multidisciplinary of learning centered on an issue or topic or theme, both theoretically and practically, and combines institutional school and outside of the school who developed an integrated program based on students?óÔé¼Ôäó need, community?óÔé¼Ôäó needs and integrate learning activities to achieve the purpose of students?óÔé¼Ôäó personality development as comprehensive and integrated. Integrating learning implemented centers based. Learning centers model focuses on playing centers in learning. Playing centers is an activity area designed inside or outside of the classroom, contains a variety of playing activities with the necessary ingredients and prepared based on the ability of the child and in accordance with the theme developed and designed in advance. Keyword: Integrated Model, Learning Center at PAUD